Megakaryocytes as the Regulator of the Hematopoietic Vascular Niche - Zhan, Huichun; Kaushansky, Kenneth (Frontiers in Oncology, 2022)
Megakaryocytes (MKs) are important components of the hematopoietic niche. Compared to the non-hematopoietic niche cells, MKs serving as part of the hematopoietic niche provides a mechanism for feedback regulation of hematopoietic stem cells (HSCs), in which HSC progeny (MKs) can modulate HSC adaptation to hematopoietic demands during both steady-state and stress hematopoiesis. MKs are often located adjacent to marrow sinusoids. Considering that most HSCs reside close to a marrow vascular sinusoid, as do MKs, the interactions between MKs and vascular endothelial cells are positioned to play important roles in modulating HSC function, and by extrapolation, might be dysregulated in various disease states. In this review, we discuss the interactions between MKs and the vascular niche in both normal and neoplastic hematopoiesis.